Democratic Redistribution and Rule of the Majority - Giacomo Corneo; Frank Neher (Center for Economic Studies and ifo Institute (CESifo), 2014)
Does redistribution in democracies cater to the will of the majority? We propose a direct empirical strategy based on survey data that needs not assume that voters are guided by pecuniary motives alone. We find that most democracies implement the median voter's preferred amount of redistribution and the probability to serve the median voter increases with the quality of democracy. However, there is a non-negligible share of democracies that implement a minority-backed amount of redistribution. Political absenteeism of the poor cannot explain such outcomes. Rather, they can be explained by the electoral bundling of redistribution with values and rights issues.
Keywords: D30; D70; H10; P16; 330; income redistribution; democracy; median-voter theorem; inequality